The Experience Of Breastfeeding Exclusively In Primapara Mothers In The District Of Lintang Kanan, Empat Lawang South Sumatra - Sukarni Stya Ningsih; Junika Repolita (CV. Inara, 2023)
Breastfeeding is a scientific process of providing breast milk (ASI) to babies optimally from at least six months to two years. Breastfeeding is a decision that is instinctively realized by a mother for the benefit of the child's growth and development in the future. The aim of the study was to obtain in-depth information about the exclusive breastfeeding experience for primiparous mothers in Lintang Kanan District, Empat Lawang Regency, South Sumatra. The research method used in this study uses a qualitative descriptive method. The sample in this study were primiparous mothers who had babies aged more than 6 months and gave exclusive breastfeeding to their babies as many as 5 participants. The results of this study can provide an overview to the public regarding the experiences of primiparous mothers in exclusive breastfeeding. Further research is needed regarding in-depth exploration of cultural aspects in exclusive breastfeeding because the behavior inherent in the mother is influenced by the cultural aspects owned and the application of the theory of maternal role attainment-becoming a mother to primiparous mothers in exclusive breastfeeding.